Estudy of the values for the employability in vocational training - Clemente Rodríguez Sabiote; José Álvarez Rodríguez; Miryam Lucena Morales (Universidad de Granada, 2011)
In a moment of economic crisis where the percentage of unemployed from among 20 to 30 years in Spain is very worrying, the youth should be more prepared that never for its insertion to the labor market, with the desire added of a lasting and worthy employment. Because of these reflections is born our desire to carry out an empirical investigation relating tothe Regulated vocational training adolescents employability of the Province of Granada whose studies be on the verge of finalizing and whose labor expectations are uncertain. But, ¿This youth is prepared to agree to this market?, ¿The form in which the life be planted is facilitated it or is complicated it?, ¿What importance they have the demands of the employers for this collective one? Through our investigation we observe up to what point affects and even what point they are prepared to agree to the labor market and we propose a series of interesting educational and pedagogical applications for the centers of vocational training.